2014
DOI: 10.1038/ismej.2014.139
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance and temporal partitioning of the activated sludge metacommunity

Abstract: The resilience of microbial communities to press disturbances and whether ecosystem function is governed by microbial composition or by the environment have not been empirically tested. To address these issues, a whole-ecosystem manipulation was performed in a full-scale activated sludge wastewater treatment plant. The parameter solids retention time (SRT) was used to manipulate microbial composition, which started at 30 days, then decreased to 12 and 3 days, before operation was restored to starting condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 60 publications
12
121
0
Order By: Relevance
“…In addition to their importance for protecting environmental and public health, engineered environments such as activated sludge have been shown to be valuable environments to study fundamental microbial ecology phenomena (Daims et al, 2006), in part due to their physical partitioning into ecological 'islands' with well-defined and monitored ecosystem functions. Wastewater microbiology has informed our understanding of community assembly mechanisms (Ofiteru et al, 2010;Wells et al, 2011;Kim et al, 2012), resilience and stability (Werner et al, 2011;Vuono et al, 2014), and identified novel microbes and metabolic pathways (Strous et al, 1999;van Kessel et al, 2015). Translating this knowledge into effective strategies for 'microbial resource management' (Verstraete et al, 2007) remains a challenge due to the high diversity and dynamics in activated sludge bioreactors, even during times of functional stability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their importance for protecting environmental and public health, engineered environments such as activated sludge have been shown to be valuable environments to study fundamental microbial ecology phenomena (Daims et al, 2006), in part due to their physical partitioning into ecological 'islands' with well-defined and monitored ecosystem functions. Wastewater microbiology has informed our understanding of community assembly mechanisms (Ofiteru et al, 2010;Wells et al, 2011;Kim et al, 2012), resilience and stability (Werner et al, 2011;Vuono et al, 2014), and identified novel microbes and metabolic pathways (Strous et al, 1999;van Kessel et al, 2015). Translating this knowledge into effective strategies for 'microbial resource management' (Verstraete et al, 2007) remains a challenge due to the high diversity and dynamics in activated sludge bioreactors, even during times of functional stability.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be clarified which environmental factors select and shape the oligotrophic bacterial populations in the perturbed MBR. Nevertheless, such functional redundancy and niche differentiation are essential for the maintenance of the microbial community function, i.e., the stabilization of reactor performances, as reported in the other wastewater treatment plants (Allison and Martiny 2008;Vuono et al 2015). On the other hand, OTU IV (Solitalea-related Flavobacteriia bacterium) showed a drastic increase after the event i, so that became the second most abundant OTU at day 22 (relative abundance 6.8 %; Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Environmental factors, such as precipitation, temperature and pH can influence cell density, waste concentration and specific nitrification rates. However, operating conditions, including organic loading rate, feed composition, reactor configuration and solids retention time (SRT) can all influence microbial diversity as well (Pholchan et al, 2010;Vuono et al, 2015). For example, a press disturbance experiment investigating reduction in SRT from 30 days to 12 or 3 days resulted in a shift in sludge microbial community composition from K-strategists to r-strategists, with demonstrated losses in bacterial diversity following the disturbances (Vuono et al, 2015).…”
Section: Wastewater Treatment Plant Characterizationmentioning
confidence: 97%
“…Once in the aeration tank, presence or absence of nutrients and cofactors , adaptation of aeration tank microbial communities to operating conditions (e.g. Vuono et al, 2015), co-metabolism with other waste streams (Fischer and Majewsky, 2014) and physiochemical environmental parameters (e.g. Pholchan et al, 2010) can all substantially influence biodegradation rates of ILs in sewage sludge.…”
Section: Enrichment Culture Characterizationmentioning
confidence: 99%
See 1 more Smart Citation